Revealing the impact of Pseudomonas aeruginosa quorum sensing molecule 2’-aminoacetophenone on the human bronchial-airway epithelium and pulmonary endothelium using a human airway-on-a-chip - Shifu Aggarwal; Shifu Aggarwal; Arijit Chakraborty; Arijit Chakraborty; Arijit Chakraborty; Vijay K. Singh; Stephen Lory; Katia Karalis; Laurence G. Rahme; Laurence G. Rahme; Laurence G. Rahme (Frontiers in Immunology)
BackgroundPseudomonas aeruginosa (PA) causes severe respiratory infections utilizing multiple virulence functions. Previous findings on the PA secreted quorum sensing (QS)-regulated small molecule, 2’-aminoacetophenone (2-AA), revealed its impact on immune and metabolic functions, favouring a long-term presence of PA in the host. However, the 2-AA’s specific effects on bronchial-airway epithelium and pulmonary endothelium remain elusive. To evaluate the spatiotemporal changes in 2AA within the human airway, considering endothelial cells as the primary point of contact when the route of lung infection is hematogenic, we utilized the airway-on-achip platform. This dynamic culture system recapitulates critical elements of the human airway microphysiological environment.MethodsWe utilized the microfluidic airway-on-chip platform, lined by polarized primary human pulmonary microvascular endothelial cells (HPMEC) and adjacent primary normal human bronchial epithelial cells (NHBE) obtained from healthy female donors. Cells exposed to 2-AA (20 μm) through continuous flow for 12 hours were used for whole-genome RNA sequencing and analyzed for their responses and potential cross-talk. Transcriptome findings were validated through in vivo studies in mice and additional cell culture experiments.ResultsAnalyses revealed that 2-AA differentially regulates specific signaling and biosynthesis pathways in epithelial cells, including HIF-1 and pyrimidine signaling, glycosaminoglycan and glycosphingolipid biosynthesis. In endothelial cells, fatty acid metabolism, phosphatidylinositol, and estrogen receptor signaling, as well as proinflammatory signaling pathways, were identified. Significant overlap was found in both cell types in response to 2-AA in genes implicated in immune response and cellular functions. In contrast, we found that genes related to barrier permeability, cholesterol metabolism, and oxidative phosphorylation were differentially regulated in response to 2-AA exposure in the studied cell types. Murine in vivo and additional in vitro cell culture studies confirmed the accumulation of cholesterol in epithelial cells. Results also revealed that specific biomarkers associated with cystic fibrosis and idiopathic pulmonary fibrosis were modulated by 2-AA in both cell types, with the expression of cystic fibrosis transmembrane regulator being affected only in endothelial cells.